Associação entre pré-natal e parto na rede de saúde suplementar e cesárea eletiva - Ferrari, Anna Paula; Carvalhaes, Maria Antonieta De Barros Leite; Parada, Cristina Maria Garcia De Lima (Associação Brasileira de Saúde Coletiva, 2016)
ABSTRACT:Objective:To identify socio-demographic factors, characteristics and pregnancy complications associated with elective cesarean section.Methods:Cross-sectional study. A total of 1,295 births in the first semester of 2012 in Botucatu, São Paulo, Brazil, were evaluated in a large epidemiological study of maternal and child morbidity and mortality. This article compares women who had normal births (n = 405) with 214 undergoing elective cesarean section, defined as scheduled and without reference in hospital records or prenatal card of absolute, relative indication or any medical reason for that. Data were obtained from hospital records, prenatal card and interview with women, soon after parturition. Univariate analysis was conducted and evaluated by Fisher's exact or χ2 tests. Variables with p < 0.20 were grouped into three blocks and, by hierarchical multiple logistic regression model, the associated factors with elective cesarean section were identified, considering p < 0.05.Results:Socio-demographic variables (age ≥ 18 years, ≥ high school education, paid work and living with a partner) were independently associated with increased odds of elective cesarean section. Regardless of these, there was an association between elective caesarean section and prenatal and place of birth, with a higher chance of birth by elective caesarean section when the woman was assisted by the supplementary health network. Taking as indicators of unfavorable socioeconomic conditions the low education, the payment of prenatal and childbirth by the Unified Health System, it can be said that there was an association between elective caesarean section and better socio-economic conditions.Conclusion:Actions in the supplementary health network are required to approach the cesarean delivery rate in the municipality to the international recommendations.

RESUMO:Objetivo:Identificar fatores sociodemográficos, características e intercorrências gestacionais associadas à realização de cesárea eletiva.Métodos:Estudo transversal. De um total de 1.295 nascimentos ocorridos no primeiro semestre de 2012 no município de Botucatu, São Paulo, avaliados em um amplo estudo epidemiológico sobre morbimortalidade materna e infantil, o presente artigo compara mulheres que tiveram partos normais (n = 405) com as 214 submetidas à cesárea eletiva, definida como agendada, sem referência no prontuário hospitalar ou cartão de pré-natal de indicação absoluta ou relativa ou a qualquer motivo de ordem médica. Os dados foram obtidos dos registros hospitalares, cartão de pré-natal e entrevista com as mulheres, logo após o parto. Realizou-se análise univariada, avaliada pelo teste exato de Fisher ou χ2. Variáveis com p < 0,20 foram então agrupadas em três blocos e, mediante modelo de regressão logística múltiplo, hierarquizado, identificaram-se fatores associados à cesárea eletiva, considerando-se p < 0,05.Resultados:Variáveis sociodemográficas (idade ≥ 18 anos, escolaridade ≥ ensino médio, trabalho remunerado e viver com companheiro) associaram-se de modo independente à maior chance de cesárea eletiva. Independente destas, houve associação entre cesárea eletiva e local de pré-natal e parto, sendo maior a chance de nascimento por cesárea eletiva quando a mulher foi assistida na rede de saúde suplementar. Tomando como indicadores de condições socioeconômicas desfavoráveis baixa escolaridade, ter pagamento do pré-natal e parto pelo Sistema Único de Saúde (SUS), pode-se afirmar que houve associação entre cesárea eletiva e melhores condições socioeconômicas.Conclusão:São necessárias ações na rede suplementar para aproximar das recomendações internacionais a taxa global de cesáreas no município.
Association between prenatal and parturition in the supplementary health network and elective cesarean section
Keywords: Prenatal care; Parturition; Cesarean section; Pathology; Social conditions; Pregnant women.; Cuidado pré-natal; Parto; Cesárea; Patologia; Condições sociais; Gestantes.